The Modulation of Stimulus Familiarity on the Repetition Effect in Duration Judgment - Jia, Lina; Deng, Can; Wang, Lili; Zang, Xuelian; Wang, Xiaocheng (Frontiers in Psychology, 2020)
The repetition of stimuli often produces a shorter subjective duration compared to the presentation of novel stimuli. To test whether familiarity mediates the repetition compression effect, the present study compared the influence of repeated words and pseudowords on apparent duration, using a duration discrimination task. We found a similar magnitude of temporal compression for the repeated-word and repeated-pseudoword conditions. When introducing a further experiment with two new conditions in which the standard-comparison pair shared a character at the first or the second constituent position, we observed a shorter subjective duration for whole words (or whole pseudowords) repetition compared to the remaining conditions (i.e., first-character repetition, second-character repetition, and novel baseline). However, temporal compression for the first- and second-character repetitions was observed for pseudowords but not for words. Our findings indicate that familiarity modulates the perception of duration in constituent character repetition. The results are discussed on the basis of the predictive coding theory.